PERAMALAN JUMLAH PENDERITA DEMAM BERDARAH DENGUE DI KOTA DENPASAR MENGGUNAKAN MODEL FUNGSI TRANSFER MULTIVARIAT - GUNAWAN, NOVIAN ENDI; SUMARJAYA, I WAYAN; SRINADI, I GUSTI AYU MADE (E-Jurnal Matematika, 2018)
Forecasting is a way to predict future events. One model in forecasting is a transfer function. The transfer function is a forecasting model that combines characteristics of the ARIMA model with some characteristics of regression analysis. Dengue Hemorrhagic Fever is a major problem in Bali. Recorded Bali Province ranked fourth in the spread of dengue virus and Denpasar City ranked first in the number of death cases of Dengue Hemorrhagic Fever. The purpose of this research is to know the multivariate transfer function model and the prediction of people with Dengue Hemorrhagic Fever in Denpasar City based on the level of rain and humidity. Forecasting results in 2017 in January to June were 46, 51, 226, 625, 1064, 1001, and 580 peoples with a percentage error model transfer function of 17.2%.